The impact of agricultural policy measures on protecting agrobiodiversity, promoting sustainable farming, and improving farmers’ incomes: A desk review of experiences from Europe - Vernooy, Ronnie (2025)
This report presents the results of a desk review about the impact of agricultural policy measures implemented in Europe for the protection of agrobiodiversity, the promotion of sustainable farming, and the improvement of farmers’ income, with a focus on the Common Agricultural Policy (CAP) of the European Union. The review concludes that over many decades, the CAP has been instrumental to support farmers across Europe financially, but this has not or hardly been realized in harmony with the conservation of agrobiodiversity and the protection of the agro-environment. Major shortcomings and some suggestions for improvement are identified.